FAKTOR-FAKTOR PENENTU PEMBERIAN ASI EKSKLUSIF PADA IBU BEKERJA: SEBUAH STUDI DI RSI SAKINAH MOJOKERTO - Mukhoirotin Mukhoirotin; Yesi Hijria Perdani; Diah Ayu Fatmawati (PT Nuansa Fajar Cemerlang, 2026)
Low rates of exclusive breastfeeding pose a threat to children’s growth and development. Being a working mother is often considered one of the factors contributing to the high rate of failure in exclusive breastfeeding. This study aims to determine the factors influencing exclusive breastfeeding among working mothers at RSI Sakinah Mojokerto. The research design used was descriptive analytic with a cross-sectional approach. The study population consisted of all working mothers with infants aged 6–24 months at RSI Sakinah Mojokerto. The sample included 43 respondents selected using a simple random sampling technique. The independent variables were knowledge, attitude, availability of breastfeeding facilities, and support from coworkers, while the dependent variable was exclusive breastfeeding. Data were collected using questionnaires and analyzed using chi-square and logistic regression tests with a significance level of α ≤ 0.05. The results showed that factors influencing exclusive breastfeeding were attitude and availability of facilities (p < 0.05). Factors that did not influence exclusive breastfeeding were knowledge and coworker support (p > 0.05). The most dominant factor was the availability of breastfeeding facilities, with an Exp(B) value of 38.916. This indicates that the availability of breastfeeding facilities in the workplace can support and facilitate mothers in providing exclusive breastfeeding. The more adequate the breastfeeding facilities available, the greater the likelihood that working mothers will successfully provide exclusive breastfeeding.